43. Motor evoked potentials monitoring for the evaluation of reversal of profound rocuronium-induced neuromuscular blockade by sugammadex in vocalis muscle. Issue 1 (January 2015) - de Scisciolo, G.; Martinelli, C.; Provvedi, E.; Gianisello, L.; Pavoni, V.
<x xml:space="preserve">Abstract</x> Recovery of paralysis of the vocalis cords is one objective of reversal agents after neuromuscular block (NMB). Sugammadex is a novel cyclodextrin, the first in a new class of selective binding reversal agents that terminates NMB with the steroidal nondepolarizing agents, rocuronium and vecuronium. We designed this study to evaluate the efficacy of sugammadex in reversing profound rocuronium-induced NMB at the laryngeal adductor muscles using recording motor evoked potentials (MEPs) from vocal muscles after transcranial electrical stimulation (TES). 5 patients undergoing propofol-remifentanil anesthesia for the surgery of the thyroid gland were enrolled for reversal of profound NMB (sugammadex 16 mg/kg, 3 min after rocuronium 1.2 mg/kg). During surgical procedures, to prevent laryngeal nerve injury, all patients underwent neurophysiologic monitoring using MEPs from vocalis muscles. After injection of 16 mg/kg of sugammadex, the means of recovery time of the basal MEPs response at the laryngeal adductor muscles was less than 1 min. In the postoperative period, no lesion to the vocalis cords caused by the surface laryngeal electrode during electrophysiological monitoring was also noted. Recovery from profound rocuronium-induced block on the larynx is fast and complete with sugammadex.